Youth involvement: Empowerment effort through child-friendly village program - Erma Kusumawardani; Serafin Wisni Septiarti (Masyarakat, Kebudayaan dan Politik, 2019)
This study aimed to describe activity within the child-friendly village program youth through participatory activities and youth empowerment. This research is a qualitative approach with a grounded theory method and setting of the research activity is the youth of the Tegalrejo District. Informants in this study include both youth and community leaders. The data collected through means of observation, documentation, and interviews. The data analysis technique used is the interactive analysis. Triangulation is done to explain the validity of the data from various sources. These results indicate that youth empowerment includes: a) the reason for the involvement of the youth including recreational interests, concern for the community, self-awareness, a stepping stone to the level of education, job readiness, and as a form of worship, b) youth empowerment seen from planning, implementation, evaluation, and even development, and c) factors supporting the involvement of the youth, their self-awareness and the support of administrators and community leaders. While the inhibiting factors such as the differences in leisure time, the impact of youth empowerment seen from the personal, academic, and vocational skills gained. Therefore, child-friendly village program it can be one of effort. To conclude, in addition to the youth program from the government, the child-friendly village program is seen to increase youth empowerment. Empowerment showed in the impact of youth involvement in the activities of the child-friendly village program.